2020
DOI: 10.1371/journal.pone.0241318
|View full text |Cite
|
Sign up to set email alerts
|

Impact of consumer confidence on the expected returns of the Tokyo Stock Exchange: A comparative analysis of consumption and production-based asset pricing models

Abstract: Most single-factor and multifactor asset pricing models constitute special cases of the consumption-based asset pricing theory, in which investors’ marginal utility is the key determinant of asset prices. However, in recent years, production-based asset pricing models have been extraordinarily successful in correctly pricing a wide range of anomaly portfolios that are typically mispriced in previous research. In parallel, research on conditioning information has contributed to significantly improve the perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 93 publications
0
7
0
Order By: Relevance
“…Our empirical results suggest that the seasonal cycle of optimism/pessimism for future economy is one of the causes of the seasonal cycle of asset prices, including stock prices. Several studies showed that consumer confidence is reflected in stock prices [ 42 44 ]. For example, Lemmon and Portniaguina [ 42 ] showed that the returns of stocks with low institutional ownership, as well as small stocks, are forecast by consumer confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our empirical results suggest that the seasonal cycle of optimism/pessimism for future economy is one of the causes of the seasonal cycle of asset prices, including stock prices. Several studies showed that consumer confidence is reflected in stock prices [ 42 44 ]. For example, Lemmon and Portniaguina [ 42 ] showed that the returns of stocks with low institutional ownership, as well as small stocks, are forecast by consumer confidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Lemmon and Portniaguina [ 42 ] showed that the returns of stocks with low institutional ownership, as well as small stocks, are forecast by consumer confidence. More specifically, Rojo-Suárez and Alonso-Conde [ 44 ] showed that consumer confidence in Japan affects the stock prices of the Tokyo Stock Exchange. Based on these studies, it seems reasonable to assume that the seasonal cycle of people’s optimism/pessimism exemplified by the CCI (AVE) is one of the causes of asset price transitions in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…Mourougane and Roma ( 2003 ), Chua and Tsiaplias ( 2009 ), and Utaka ( 2014 ) consider the CCI a relevant predictor of the short-term growth in gross domestic product. Lemmon and Portniaguina ( 2006 ), Chen ( 2011 ), Hsu et al ( 2011 ), and Rojo-Suárez and Alonso-Conde ( 2020 ) indicate that changes in the consumer confidence Granger-cause stock returns. Vuchelen ( 2004 ), Kwan and Cotsomitis ( 2006 ), Mandal and McCollum ( 2013 ), Kłopocka ( 2017 ), Pan ( 2018 ), Karasoy Can and Yüncüler ( 2018 ), Claveria ( 2019 ), and Acuña et al ( 2020 ) found a negative causality between the consumer confidence and the unemployment rate both in the short run and long run.…”
Section: Consumer Confidence and Its Measurementmentioning
confidence: 99%
“…They provide a range of entropy measurements. In the case of [ 20 ] For the capital asset assessment model and the Fama French three and five factor models, their results reveal that the entropy piece is indisputably compared to the GLS R2 estimate [ 21 ]. When a quantile relapse increases, the CAPM beta danger turns into a varied positive.…”
Section: Literature Reviewmentioning
confidence: 99%